Bridging traditional knowledge and usage of Anupana for "Gopalu guliya": Review on Traditional Polyherbal Formulation: Hapuarachchi S.D.* and Gunawadhana R.M.R (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2024)
Sri Lanka has a distinctive system of traditional medicine, which has a considerable impact on the cultural and medical history of the island. The Gopalu guliya is one of the most effective traditional formulations. It has been used in many disease conditions with different Anupana (Drug delivery vehicles) in Sri Lankan traditional medicine (SLTM), but now it is rare. The objectives of the study are to explore the traditional knowledge of Gopalu guliya, and Xylocarpus rumphii (Kostel.) Mabb (Konthalan) and their uses in various disease conditions, to examine drug delivery approaches and their impact on medicinal efficacy, and to emphasize the importance of conserving X. rumphii. The study is based on 4 original texts and 13 previously published journal articles from databases including Scopus, Web of Science, PubMed, and Lens.Org using search terms “Xylocarpus rumphii” from 2010 to 2023. This article includes the formulations, therapeutic applications, and drug delivery approaches of Gopalu guliya in Sri Lankan Ayurveda Pharmacopoeia, Desheeya Guli Kalka Sagaraya, Visha Veda Muthu hara, and Aushadeeya Shaka Sangrahaya. X. rumphii, the most weighted ingredient of Gopalu guliya, is the primary contributor to its distinguishing characteristics. The ethnomedicinal properties of Gopalu guliya and X. rumphii are also discussed, highlighting their significance. The Red Data Book (2022) lists X. rumphii, highlighting its importance in conservation. The study highlights the propagation methods of X. rumphii, urging for conservative measures, research, and collaborative initiatives to protect these valuable resources and ensure sustainable healthcare with traditional polyherbal formulation Gopalu guliya.